2008
DOI: 10.3386/w14104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Income on the Weight of Elderly Americans

Abstract: SUMMARYThis paper estimates the impact of income on the body weight and clinical weight classification of elderly Americans using a natural experiment that led otherwise identical retirees to receive significantly different Social Security payments based on their year of birth. We estimate models of instrumental variables using data from the National Health Interview Surveys and find no significant effect of income on weight. The confidence intervals rule out even moderate effects of income on weight and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…Neither the Social Security payments examined by Cawley et al (2010) nor the casino payments examined by Akee et al (2013) were means tested, but the affected groups were relatively lower-income; Social Security beneficiaries tend to have lower earned income (though greater wealth) than working-age adults and Native Americans have a lower median income and higher poverty rate than the nation as a whole (U.S. Census Bureau, 2011). The EITC recipients examined by Schmeiser (2009) are unambiguously a low-income group.…”
Section: Incomementioning
confidence: 99%
See 1 more Smart Citation
“…Neither the Social Security payments examined by Cawley et al (2010) nor the casino payments examined by Akee et al (2013) were means tested, but the affected groups were relatively lower-income; Social Security beneficiaries tend to have lower earned income (though greater wealth) than working-age adults and Native Americans have a lower median income and higher poverty rate than the nation as a whole (U.S. Census Bureau, 2011). The EITC recipients examined by Schmeiser (2009) are unambiguously a low-income group.…”
Section: Incomementioning
confidence: 99%
“…The authors find evidence of the non-linearity of weight in income; the payments increase BMI among adolescents from low-income households but have no impact on weight for adolescents in higher-income households. Cawley et al (2010) estimate the effect of income on weight among the elderly, exploiting the natural experiment of the Social Security Benefits Notch, which was a legislative accident that created substantial unanticipated increases in retirement benefits (averaging roughly $1000 in each year of retirement) for certain birth year cohorts in the United States. The authors find no statistically significant impact of income on BMI or the probability of obesity for either men or women, and for men they find precisely estimated zero effects.…”
Section: Incomementioning
confidence: 99%
“…Evidence of income effects on health behaviors is mixed (e.g., Cawley & Ruhm, ; Johnson, Parker, & Souleles, ; Parker et al., ). To take the example of weight, studies have found that income increases BMI among lower‐income youths (Akee et al., ) and lower‐income women (Schmeiser, ) but not among lower‐income men (Schmeiser, ) or Social Security recipients (Cawley, Moran, & Simon, ). In summary, health insurance coverage may affect health behaviors through multiple channels; the net impact is theoretically ambiguous and thus is ultimately an empirical question.…”
Section: Introductionmentioning
confidence: 99%
“…() find permanent increases in income reduce obesity, whereas Cawley et al . () finds no income effects on obesity. In a recent study concentrating on adolescents, Akee et al .…”
Section: Introductionmentioning
confidence: 94%
“… A possible reason for the different conclusions is that they have focussed on different populations, such as the elderly (Cawley et al ., ; Kim and Ruhm, ), adolescents (Akee et al ., ), low‐income households (Schmeiser, ), lottery players (Lindahl, ) and American Indians (Wolfe et al ., ). Another explanation is that different empirical approaches have been used to identify the causal effects.…”
mentioning
confidence: 99%